2019
DOI: 10.1186/s13104-019-4260-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of palliative care for patients with terminal diseases from the viewpoint of healthcare personnel

Abstract: Objective In Indonesia, palliative care has not been uniformly implemented at all levels of healthcare facilities. Healthcare personnel play an important role in providing that care. This study aimed to explore the current conditions and expectations regarding palliative care from the perspective of healthcare personnel. Results A qualitative study was conducted with 12 physicians and five nurses from December 2017 to June 2018. In-depth interviews of these professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…A previous report described the use of mHealth services by midwives collaborating with CHWs [ 16 ]. Some studies have noted the use of mHealth to help provide healthcare services for patients and families [ 7 ], including for palliative care [ 17 , 18 ], which further highlights the pivotal role of mHealth [ 19 ]. A recent literature review identified that data collection may be the main challenge in many community programs and that using mHealth should be included in the training of CHWs [ 9 ] so they can provide more effective support [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous report described the use of mHealth services by midwives collaborating with CHWs [ 16 ]. Some studies have noted the use of mHealth to help provide healthcare services for patients and families [ 7 ], including for palliative care [ 17 , 18 ], which further highlights the pivotal role of mHealth [ 19 ]. A recent literature review identified that data collection may be the main challenge in many community programs and that using mHealth should be included in the training of CHWs [ 9 ] so they can provide more effective support [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Practice is described by 5 domains and 20 questions. 1 The domains are case notification (4 questions), comprehensive and integrated care (10 questions), follow up (2 questions), and interdisciplinary collaboration (4 questions). Response categories for all items included yes, sometimes and never.…”
Section: Methodsmentioning
confidence: 99%
“…1,[5][6][7][8] In some countries, palliative care has been not implemented yet due to limited number of trained health workers. 1 One study highlights that only physicians who were interested in the end of life care have good knowledge regarding the care. 6 Health workers who demonstrate optimal practice in palliative care had a stronger effect to patient's outcome.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a record of the use of mHealth by midwives collaborating with CHWs (16). Some studies identi ed mHealth use to help healthcare services for patients and families (6), including for palliative care (17,18), which also highlights its pivotal role (19). A recent literature review proposes that data collection is the main challenge and that it should be included in CHWs' skills training to support many community programs by using mHealth (8) so that they may provide more effective support (20).…”
Section: Introductionmentioning
confidence: 99%